Tunable Spin Characteristic Properties in Spin Valve Devices Based on Hybrid Organic–Inorganic Perovskites. Issue 41 (27th August 2019) - Wang, Jingying; Zhang, Chuang; Liu, Haoliang; Liu, Xiaojie; Guo, Hangwen; Sun, Dali; Vardeny, Zeev Valy
Abstract: The hybrid organic–inorganic perovskites (HOIPs) form a new class of semiconductors which show promising optoelectronic device applications. Remarkably, the optoelectronic properties of HOIP are tunable by changing the chemical components of their building blocks. Recently, the HOIP spintronic properties and their applications in spintronic devices have attracted substantial interest. Here the impact of the chemical component diversity in HOIPs on their spintronic properties is studied. Spin valve devices based on HOIPs with different organic cations and halogen atoms are fabricated. The spin diffusion length is obtained in the various HOIPs by measuring the giant magnetoresistance (GMR) response in spin valve devices with different perovskite interlayer thicknesses. In addition spin lifetime is also measured from the Hanle response. It is found that the spintronic properties of HOIPs are mainly determined by the halogen atoms, rather than the organic cations. The study provides a clear avenue for engineering spintronic devices based on HOIPs. Abstract : The spintronic properties of different hybrid organic–inorganic perovskites (HOIPs) are studied in spin valve devices, including spin diffusion length and spin lifetime, as well as the impact of the chemical components on these properties. This study aims at demonstrating promising spintronic applications of HOIPs, and providing a clear path for engineering spintronic devices based on HOIPs.